Gerakan Perempuan di Indonesia Dari Masa ke Masa - Muhadjir Darwin (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Examination to Indonesia's current history shows that woman-movement is always exist from time to time. Gender equality, indeed has not been openly declared as mission of the movements. The author argues, however, that gender equality has been manifest in the spirit of shared-responsibility in overcoming the problems of the country defined at each era.